The Impact of NPF Ratio, FDR, BOPO, Inflation Rate, And Depositor Funds of Conventional Banks To The Total Assets Of Sharia Banks In Indonesia - B01112001, Syeda Zakia (Jurnal Pembangunan dan Pemerataan, 2016)
This research aimed to find out and measure the impact of Non-Performing Financing (NPF) ratio, Finance to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), rate of inflation, and the Third Party Funds (DPK) of Conventional Banks on the total assets of Sharia Banks in Indonesia, as a proxy of the growth of Sharia banking. The data used were time series and collected from the publication of Bank Indonesia from January 2010 to December 2014.The method of analysis used in this research was tthe multiple regression analysis using the Ordinary Least Squares (OLS) technique with the E-Views 7 application. From five variables, only three had a significant impact, i.e. NPF ratio wich had negative and significant impact, FDR wich had a positive and significant impact, and the Third Party Funds (DPK) of conventional banks which also had a positive and significant impact. Menawhile, the BOPO and rate of inflation are variables that did not have a significant impact on the total assets of Sharia Banks in Indonesia during the period from January 2010 to December 2014.Keywords: Sharia banking, conventional banking, total assets, NPF, FDR, BOPO, inflation, DPK